Dynamic spatial beam shaping for ultrafast laser processing: a review - Mauclair, Cyril; Najih, Bahia; Comte, Vincent; Bourquard, Florent; Delaigue, Martin (Opto-Electronic Science, 2025)
This review examines the state-of-the-art in spatial manipulation of ultrafast laser processing using dynamic light modulators, with a particular focus on liquid crystal-based systems. We discuss phase modulation strategies and highlight the current limitations and challenges in surface and bulk processing. Specifically, we emphasize the delicate balance between high-fidelity beam shaping and energy efficiency, both critical for surface and bulk processing applications. Given the inherent physical limitations of spatial light modulators such as spatial resolution, fill factor, and phase modulation range. We explore techniques developed to bridge the gap between desired intensity distributions and actual experimental beam profiles. We present various laser light modulation technologies and the main algorithmic strategies for obtaining modulation patterns. The paper includes application examples across a wide range of fields, from surgery to surface structuring, cutting, bulk photo-inscription of optical functions, and additive manufacturing, highlighting the significant enhancements in processing speed and precision due to spatial beam shaping. The diverse applications and the technological limitations underscore the need for adapted modulation pattern calculation methods. We discuss several advancements addressing these challenges, involving both experimental and algorithmic developments, including the recent incorporation of artificial intelligence. Additionally, we cover recent progress in phase and pulse front control based on spatial modulators, which introduces an extra control parameter for light excitation with high potential for achieving more controlled processing outcomes.